2015
DOI: 10.1136/bmjquality.u206272.w2608
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the Pre-Operative Investigative Work Up for Elective Surgical Patients

Abstract: Effective pre-operative assessment of patients awaiting elective surgery should entail appropriate use of scarce NHS resources, as well as underpin patient safety. The pre-operative admissions service in district general hospitals is often junior doctor led, with a new cohort of clinicians taking over its running every four months. Lack of familiarity on the part of these clinicians with the investigative work up required for certain surgical procedures often results in over investigation of patients in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…All the abstracts were screened and 15 full-text articles [11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] strictly met the study inclusion criteria-a total of 477,437 patients. All were retrospective studies: 10 studies [11,19,21,23,[25][26][27][28][29][30] reviewed the necessity of G&S for cholecystectomy procedures only, two studies [31,32] on appendectomy procedures only and three studies [20,22,24] evaluated both procedures. A PRISMA [33] flowchart of the section process for this study is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the abstracts were screened and 15 full-text articles [11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] strictly met the study inclusion criteria-a total of 477,437 patients. All were retrospective studies: 10 studies [11,19,21,23,[25][26][27][28][29][30] reviewed the necessity of G&S for cholecystectomy procedures only, two studies [31,32] on appendectomy procedures only and three studies [20,22,24] evaluated both procedures. A PRISMA [33] flowchart of the section process for this study is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cholecystectomy is safe with a low transfusion rate. O negative blood has already been screened for the presence of most significant non-ABO antibodies Yes Hack-Adams et al [ 25 ], 2015 Patients over investigated and routine G&S testing should be eliminated Yes Hamza et al [ 11 ], 2015 Routine G&S is unnecessary Yes Li and Low [ 26 ], 2020 A preoperative G&S test did not impact management for any patients undergoing laparoscopic cholecystectomy. It should not form part of the routine work-up, although it may still be required for high-risk cases Yes Lin et al [ 27 ], 2006 G&S may be safely disregarded Yes Magowan et al [ 32 ], 2020 G&S tests are unnecessary and ceasing their requirement as standard may result in significant financial savings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2016 National Institute for Health and Care Excellence (NICE) guidelines, which aimed to standardise the process of pre-operative investigation across the United Kingdom (UK), emphasised the reduction of unnecessary pre-operative testing [23]. Several UK publications have similarly concluded that routine Group and Save sampling for laparoscopic cholecystectomy is "unnecessary" [19,[24][25][26]. The 2012 French Society of Anaesthesiology and Intensive Care (SFAR) guidelines, which were endorsed by 17 surgical and medical scientific societies, also highlighted the need to reduce redundant pre-operative tests, advising against the routine use of Group and Save sampling in low-risk patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…
Preoperative investigations are important elements of preoperative evaluation to determine the fitness for anaesthesia and surgery. [1,2,3]. The objectives were to assess the number of unnecessary preoperative investigations carried out and repeated in Dental Hospital, Peradeniya and to analyze the cost of investigations that are performed unnecessarily.
…”
mentioning
confidence: 99%